EFFECT OF VAM FUNGI ON PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITY IN SOLANUM SURATTENSE L. - Pria, S; Shanmugapriya, O.N. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
In this study six fungal species were isolated from soil samples. Among the six species Glomus fasiculatum and Gigaspora marigarita noted in dominant level. So both are used as bioinoculant and were mass multiplied in onion plant by pot culture. After pot culture, biochemical and antibacterial activity were analysed from the treated plant Solanum surattense. In the phytochemical analysis falvonoids, tannins , terpenoids, cardiac glycosides and saponins were noted. Antibacterial activity of ethanolic extract of Solanum surattenseÂ against clinical isolates were analyzed and show the more activity noted in K.pneumoniae when compared with Bacillus subtilis, Streptococcus pyogens, E.coli respectively.